Recruiting volunteers for humantarian via advertising campaign / Nurul Ainun Alimudin - Alimudin, Nurul Ainun (Faculty of Art and Design, 2013)
This new campaign is a new way to get or recruiting volunteer for preparation. As we know it is like an infinity force. The volunteer is needed as there are never ending. But, as getting started as a new phase in Malaysia, the Humankind program that going to be created is more like an awareness campaign. As for Mercy Malaysia itself, they need more volunteer. In these few years, Mercy Malaysia is well-known NGO. Beside that, they have been serviced for many humanitarian jobs regardless of race, religion, culture or boundary